High-sensitivity C-reactive protein is not a risk factor for venous thromboembolism: the Tromso study - Hald, Erin Mathiesen; Brækkan, Sigrid Kufaas; Mathiesen, Ellisiv B.; Njølstad, Inger; Wilsgaard, Tom; Brox, Jan; Hansen, John-Bjarne (Haematologica, 2011)
This article is part of Eirin Hald's doctoral thesis, which is available in Munin at http://hdl.handle.net/10037/7006 High-sensitivity C-reactive protein is associated with risk of arterial cardiovascular disease but conflicting results have been reported on its role in venous thromboembolic disease. The objective of our study was to investigate the association between high-sensitivity C-reactive protein levels and risk of future venous thromboembolism in a prospective cohort recruited from a general population. High-sensitivity C-reactive protein was measured in serum samples from 6,426 men and women, aged 25-84 years, recruited from the Tromsø Study in the period 1994-1995. Incident venous thromboembolism events (n=209) were registered during a median of 12.5 years of follow up. Cox’s proportional hazards regression models were used to estimate age- and genderand multivariable-adjusted hazard ratios with 95% confidence intervals for total venous thromboembolism, and for provoked and unprovoked venous thromboembolism by increasing levels of high-sensitivity C-reactive protein. There was no increased risk of venous thromboembolism per 1 standard deviation increase in high-sensitivity C-reactive protein (hazard ratio 1.08; 95% confidence interval 0.95-1.23) or across quartiles of high-sensitivity C-reactive protein (P for trend 0.6) in analyses adjusted for age and gender. Further adjustment for body mass index, smoking and diabetes did not alter the risk estimates. Moreover, high-sensitivity C-reactive protein was not associated with venous thromboembolism in either gender specific analysis or in separate analyses of provoked and unprovoked venous thromboembolism events. In this prospective study, serum levels of high-sensitivity C-reactive protein were not associated with future development of venous thromboembolism. Our findings do not suggest a causal role for C-reactive protein in the pathogenesis of venous thromboembolism.